Prevalence of Fatigue in Head and Neck Cancer Survivors. (May 2019) - Bossi, Paolo; Di Pede, Patricia; Guglielmo, Mauro; Granata, Roberta; Alfieri, Salvatore; Iacovelli, Nicola Alessandro; Orlandi, Ester; Guzzo, Marco; Bianchi, Roberto; Ferella, Letizia; Infante, Gabriele; Miceli, Rosalba; et al.
Introduction: In head and neck cancer (HNC) patients, fatigue is present throughout the course of treatment and during follow-up. There are limited data about the prevalence and factors associated with fatigue in HNC survivors. The objectives of this study were to assess the prevalence of fatigue and its interference with daily life activities and examine the association between fatigue and gender, age, primary tumour site, Human Papillomavirus (HPV) status, previous oncologic therapy, and time since end of treatment. Methods: Consecutive locally advanced HNC patients having completed curative treatment at least 1 year earlier and free of disease were asked to fill in the Brief Fatigue Inventory (BFI) questionnaire. Fatigue was categorized according to BFI average score as absent (0), mild (>0 to <4), moderate (≥4 to ≤6), and severe (>6 to ≤10). Results: From February 2015 to July 2016, 129 patients (median age = 60 years old; 67% male) were evaluated. Primary sites of cancer were oropharynx (46%, with 4/5 patients HPV positive), nasopharynx (22%), larynx/hypopharynx (14%), oral cavity (13%), and paranasal sinus or salivary gland (5%). Oncologic treatment was completed 12 to 96 months earlier (median = 34 months). Fatigue was reported as absent in 15% of the patients, mild in 67%, moderate in 11%, and severe in 7%. No association between BFI average score and the analyzed variables was identified. Discussion: Moderate and severe fatigue was reported in 18% of HNC survivors. Further research is needed to assess its causes and improve the management.